The psychological impact and functional disability of patients with acne vulgaris in Hospital Serdang, Malaysia: a cross sectional analysis - How, Kang Nien; Shamsudin, Norashikin (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Acne vulgaris is not only associated with physical morbidity, but also associated with significant psychosocial disturbances, such as depression and suicide. The objective of this study was to examine the functional disability and psychological impact of acne vulgaris. Methods: A cross-sectional study of 55 acne patients, aged more than 12, was conducted in the dermatology clinic of Serdang Hospital from January to March 2017. Data on demographics, clinical features, current treatment modalities were collected. Acne severity was graded using Comprehensive Acne Severity Scale (CASS), Cardiff Acne Disability Index (CADI) was used to assess functional disability, while DASS-21 was used to assess three related states of depression, anxiety and stress. Statistical analysis was done using SPSS software. A p value ≤ 0.05 considered significant. Results: The mean age was 23.2 (14-46), majority were females (39, 70.9%), Malays (44, 80%) and students (34, 61.8%). 53 (96.4%) subjects had almost clear (CASS = 1) to moderate (CASS = 3) acne severity. Majority had facial acne with or without truncal involvement, 53 (96.3%). The average age of disease onset was 17.8 (9-45). 45 (81.8%) patients found their acne mild to moderately disabling. 69.1%, 45.8% and 41.8% reported feeling anxious, depressed and stressed out. CADI was found to be significantly related with depression (p=0.012), anxiety (p= 0.015) and stress (p=0.001). Relationship between CASS with CADI (p=0.07), stress (p=0.09), anxiety (p=0.13) and depression (p=0.12) were insignificant. Conclusion: Although acne vulgaris is not hazardous, it is associated with psychosocial disturbances. Early and effective treatments are necessary, especially when dealing with facial lesions.